2020
DOI: 10.1101/2020.04.27.20082347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The natural history and transmission potential of asymptomatic SARS-CoV-2 infection

Abstract: 248 2 1 Main text: 2788 2 2 Running title: Asymptomatic SARS-CoV-2 infection 2 3 ABSTRACT 2 5 Background 2 6Little is known about the natural history of asymptomatic SARS-CoV-2 infection or its 2 7 contribution to infection transmission. 2 8 Methods 2 9We conducted a prospective study at a quarantine centre for COVID-19 in Ho Chi Minh City, 3 0 Vietnam. We enrolled quarantined people with RT-PCR-confirmed SARS-CoV-2 infection, 3 1 collecting clinical data, travel and contact history, and saliva at enrolment an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 22 publications
5
102
0
Order By: Relevance
“…Notably, our "optimistic" scenario is more pessimistic than many earlier studies of contact tracing because we assume higher values for both the rate and relative infectiousness of asymptomatic carriers based on numerous recent studies (5,10,27,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our "optimistic" scenario is more pessimistic than many earlier studies of contact tracing because we assume higher values for both the rate and relative infectiousness of asymptomatic carriers based on numerous recent studies (5,10,27,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Saliva has been shown to contain severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in infected individuals 22,23 , many of whom may be asymptomatic 24 , with the salivary gland potentially being an early reservoir of infection 25,26 . Equally, however, preliminary data suggest that in asymptomatic carriers, the viral load may be low in saliva and these individuals may have faster viral clearance 27,28 . Early data suggest that SARS-CoV-2 can remain viable and infectious in aerosol for hours, and on surfaces for days 29 .…”
Section: Introductionmentioning
confidence: 99%
“…(14) In addition, it is possible that PCR-based testing has a lower sensitivity for asymptomatic infections, which would further increase the proportion of asymptomatic infections. (32) A sensitivity analysis showed that our results were robust to age-specific probabilities of progressing to asymptomatic infections, as well as other assumptions made by the model, and driven by trends in the data.…”
Section: Comparison To Other Studiesmentioning
confidence: 57%
“…(30) cruise While SARS-CoV-2 has been shown to survive on surfaces, (31) but this does not seem to be the primary mode of transmission. In combination with growing evidence around viral load in asymptomatic infections and their involvement in transmission chains (14), anecdotal evidence about transmission from asymptomatic individuals (19,32) including in closed populations, (33) it is reasonable to assume that asymptomatic infections play some role in ongoing SARS-CoV transmission. In our model, 83% of scenarios compatible with the data, asymptomatic infections were responsible for more than half of all transmission.…”
Section: Discussionmentioning
confidence: 99%